The Role of Local Government in Organizing Social Security for Employment: A Comparative Case Study Between Cities and Regencies - Chyntia Rolanda Sihaloho; Clara Rina Silitonga; Evlin Novianti Tambunan; Galuh Wulandari; Gantina Sari Batubara; Habieb Pahlevi; Khairunnajmi Agustina Syahira; Radot Situmorang; Sara Klaudya Laiya; Siti Aminah Safitri (Contemporary Journal of Applied Sciences, 2024)
Various risks and uncertainties in the world of work become obstacles to workers' productivity in carrying out their duties. In this case, social security for workers acts as a form of protection for workers' social rights from various risks that may occur during the work period. This study aims to determine the role of local governments in cities and districts in implementing social security programs for workers and what challenges are faced in implementing the program. The type of research used in this study is normative legal research, namely a type of legal research methodology that bases its analysis on applicable laws and regulations that are relevant to the legal problems that are the focus of the research. In addition, this study also uses secondary data obtained from references in the form of journals, writings, websites, and other sources. The conclusion of this study is that local governments have a very important role in implementing social security for workers by linking central policies and implementation at the local level. This role includes socialization, regulation, supervision, provision of access, and infrastructure. So that synergy is needed between the central government, local governments, and various related parties to ensure that all workers can be protected by the social security program for workers.